Plastidial and ER Triacylglycerol Biosynthesis in a Growth Phase-Dependent Manner in the Heterokont Nannochloropsis oceanica - Huang, Dan; Li, Da-Wei; Balamurugan, Srinivasan; Zheng, Jian-Wei; Liu, Wan-Jun; Zou, Li-Gong; Yang, Wei-Dong; Liu, Jie-Sheng; Li, Hong-Ye (Frontiers in Marine Science, 2020)
Though microalgae have been considered the potential resource for lipid production, native strains are unable to meet the industrial demand. Here, we aim to uncover the complex molecular relationship between algal growth and lipid accumulation. Transcriptomic analysis revealed the crucial role of plastidial fatty acid and triacylglycerol (TAG) biosynthetic machinery in lipid overproduction. The expression of key fatty acid biosynthetic genes such as acetyl-CoA carboxylase (ACCase), malonyl CoA‐acyl carrier protein transacylase (MCAT), 3-ketoacyl synthase (KAS), 3-ketoacyl-ACP reductase (KAR) increased during day 10-13 of cultivation, particularly plastidial TAG biosynthetic genes substantially increased. However, expression of genes involved in ER TAG biosynthesis increased only in the stationary phase, which implied the potential of plastidial TAG biosynthesis. This report provides a novel insight into the growth-phase dependent lipogenic orchestration, and also uncovers the signature genes and plastidial TAG biosynthesis that might be extrapolated for improving lipogenic traits of algae.